The Experiences of Nurses Serving as Medical Volunteers in the Disaster Emergency Response Phase - Hidayati, Nur; Maghfiroh, Laela Khomisah; Kusbiantoro, Dadang; Sandi, Yudisa Diaz Lutfi (Babali Nursing Research, 2025)
Introduction: Indonesia in Ring of Fire is one of 35 countries worldwide facing potentially affected by various natural disasters. The disaster management phases commence with pre-disaster preparedness, emergency response, and post-disaster recovery. Nurses are the frontline healthcare professionals involved in disaster management, particularly during the emergency response phase. This study aims to describe nurses’ experiences as medical volunteers in the disaster emergency response phase. Methods: A qualitative exploratory design was carried out with a descriptive phenomenological approach. This research engaged 11 nurses from Lamongan City who participated in disaster responses team across settings level selected by purposive sampling. Data collection occurred through in-depth interviews conducted from February to March 2024. This study followed COREQ guideline to report all process Results: We identified six main themes were: 1) Reasons to volunteer; 2) Roles in disaster response; 3) Challenges; 4) Volunteering Experiences; 5) Institutional support; and 6) Valuable lesson. Conclusion: The role of nurses in disaster response expands beyond healthcare functions to cover various non-medical duty to the continuity of disaster management processes. Nurses able to contribute to non-medical schemes such as public kitchens, logistics support, and assisting search and rescue teams in victim search and evacuation processes.